A closer comparison of early and late-winter atmospheric trends in the northern hemisphere - Hu, YY; Tung, KK; Liu, JP (Journal of Climate, 2005)
Decadal trends are compared in various fields between Northern Hemisphere early winter, November-December (ND), and late-winter, February-March (FM), months using reanalysis data. It is found that in the extratropics and polar region the decadal trends display nearly opposite tendencies between ND and FM during the period from 1979 to 2003. Dynamical trends in late winter (FM) reveal that the polar vortex has become stronger and much colder and wave fluxes from the troposphere to the stratosphere are weaker, consistent with the positive trend of the Arctic Oscillation (AO) as found in earlier studies, while trends in ND appear to resemble a trend toward the low-index polarity of the AO. In the Tropics, the Hadley circulation shows significant intensification in both ND and FM, with stronger intensification in FM. Unlike the Hadley cell, the Ferrel cell shows opposite trends between ND and FM, with weakening in ND and strengthening in FM. Comparison of the observational results with general circulation model simulations is also discussed. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000232051600008&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Meteorology & Atmospheric Sciences SCI(E) EI 14 ARTICLE 16 3204-3216 18